Measuring Practicing and Prospective Elementary Teachers’ Efficacy for Classroom Management: A Preliminary Development and Validation Study - Putman, S. Michael (Alberta Journal of Educational Research, 2014)
Research has shown efficacy exerts a powerful influence on behavior. Classroom management represents one vehicle for demonstrations of these behaviors, yet few instruments focus solely on the measurement of this domain-specific form of efficacy. This research explored the relationship between teacher self-efficacy and classroom management through the development and validation of the Efficacy for Classroom Management Scale (ECMAN). Results indicated two factors may contribute to teachers’ self-efficacy for classroom management. Additional analyses revealed scores on ECMAN were correlated with a previously validated instrument for measuring efficacy. Implications are described relative to additional validation efforts and prospective uses for the instrument. La recherche a démontré que l’efficacité exerce une grande influence sur le comportement. Alors que la gestion de la classe représente une façon de démontrer ce comportement, peu d’outils portent uniquement sur l’évaluation de cette forme d’efficacité spécifique au domaine. Cette recherche a exploré le rapport entre l’auto-efficacité des enseignants et la gestion de la classe par une échelle nommée Efficacy for Classroom Management Scale (Échelle de l’efficacité en gestion de classe - ECHAM). Les résultats indiquent que deux facteurs pourraient contribuer à l’auto-efficacité des enseignants relativement à la gestion de la classe. Des analyses complémentaires ont établi une corrélation entre les résultats obtenus avec l’échelle ECHAM et des résultats découlant d’un instrument déjà validé et mesurant l’efficacité. Nous discutons des incidences relatives à d’autres efforts de validation et des emplois éventuels pour l’instrument.